(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Design of prototype robot vacuum cleaner based on Arduino Uno aims to produce a prototype robot that has the ability as a tool to clean house floor vacuum cleaners quickly and efficiently. Robot Vacuum Cleaner is designed as a vacuum cleaner and dirt on the floor of a room, which is operated using dual mode that is automatically and manually. Automatic mode on the robot vacuum cleaner will cause the robot to move randomly on the floor of a room and automatically avoid obstacles that are in front of the robot. Whereas in manual mode the robot vacuum cleaner moves following commands that are controlled by the user via an Android-based smartphone using the Bluetooth HC-05 communication module. Sharp GP sensor mounted on the robot functioned as a sensor to avoid obstacles when cleaning the floor of the house. The program flow begins by connecting the Android Smartphone to the Bluetooth HC-05 module, then Arduino will read the input data of the mode selected by the user, which is automatic or manual mode. If automatic mode is selected, Arduino will initialize the Sharp GP proximity sensor to detect the distance of objects in front of the robot and activate the vacuum motor. If the distance of the object in front of the robot more than 8 cm the robot will stop and turn directions to avoid the object. If the user chooses manual mode, the robot will wait for the user’s command to maneuver and activate the controlled vacuum motor using the application on the user’s smartphone.